2016
DOI: 10.1371/journal.pcbi.1005180
|View full text |Cite
|
Sign up to set email alerts
|

Topology, Cross-Frequency, and Same-Frequency Band Interactions Shape the Generation of Phase-Amplitude Coupling in a Neural Mass Model of a Cortical Column

Abstract: Phase-amplitude coupling (PAC), a type of cross-frequency coupling (CFC) where the phase of a low-frequency rhythm modulates the amplitude of a higher frequency, is becoming an important indicator of information transmission in the brain. However, the neurobiological mechanisms underlying its generation remain undetermined. A realistic, yet tractable computational model of the phenomenon is thus needed. Here we analyze a neural mass model of a cortical column, comprising fourteen neuronal populations distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 82 publications
(128 reference statements)
0
27
0
Order By: Relevance
“…A recent study concluded that the network topology, the CFC and the intra-frequency interactions shaped the PAC generation in a cortical column using a novel neural mass model (Sotero, 2016 ). Here, in order to reduce the computational time needed to run the pipeline from the reviewers in order to evaluate the whole analysis, we did not run surrogate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study concluded that the network topology, the CFC and the intra-frequency interactions shaped the PAC generation in a cortical column using a novel neural mass model (Sotero, 2016 ). Here, in order to reduce the computational time needed to run the pipeline from the reviewers in order to evaluate the whole analysis, we did not run surrogate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of nonlinearities in our model causes several control tasks to fail for each subject, a fact that, to the best of our knowledge, has not been reported for linear brain dynamics. However, we do not expect that inputs to every neuronal conglomerate in real stimulation experiments are able to steer the (AD) brain to the desired state, given its complexity and nonlinear character [ 18 20 ]. The order in which areas were ranked according to the energy used for controlling the network, changed with the strength of the nonlinearity, γ .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have focused on identifying the most suitable sites for network controllability from a structural viewpoint only [ 17 ] while simplifying the dynamical interactions occurring on top of the connectivity scaffold. Other studies [ 9 12 ] used linear dynamics to model neural processes, which are known to be intrinsically nonlinear [ 13 , 18 20 ]. Hence, their predictions on neural network control should be taken with caution.…”
Section: Introductionmentioning
confidence: 99%
“…Components are different as to conveyance of information (Sotero, 2016). For notation purposes, IMF1 denotes the fastest mode (highest frequency).…”
Section: The Network's Signalmentioning
confidence: 99%